Effect of Tight Junction-Modulating FCIGRL-Modified Peptides on the Intestinal Absorption of Doxorubicin in Rats - Keon-Hyoung Song (MDPI AG, 2024)
Doxorubicin is a potent chemotherapy drug, but its oral bioavailability is limited due to its low membrane permeability. Thus, absorption enhancers such as zonula occludens toxin and its six-mer fragment, FCIGRL, have been studied to address this issue. This study aimed to evaluate the effectiveness of four peptides (Pep1, Pep2, Pep3, and Pep4) derived from FCIGRL and investigate the changes in the absorption of doxorubicin, to propose an absorption enhancer for doxorubicin. Pep1 is a modified version of FCIGRL in which the hydroxyl group at the C-terminus is replaced with an amino group. Pep2 is a modified Pep1 in which cysteine is replaced with N3-substituted dipropionic acid. Pep3 and Pep4 are Pep2-modified homodimers. Pharmacokinetic analysis was performed in rats after the intraduodenal administration of doxorubicin solutions containing each FCIGRL-modified peptide and the stabilizer levan or benzalkonium chloride (BC). The results showed that Pep3 and Pep4 administered with levan each significantly increased the intestinal absorption of doxorubicin, as did Pep2 administered with levan/BC. In particular, 10 mg·kg−1 of Pep4 with levan significantly increased the area under the curve (AUC)0-240min of doxorubicin by 2.38-fold (p < 0.01) and the peak concentration (Cmax) by 3.30-fold (p < 0.01) compared to the control solution. The study findings indicate that Pep2, Pep3, and primarily Pep4 are novel absorption enhancers that can open tight junctions for doxorubicin, and the effectiveness of the peptides was directly affected by the presence of levan or levan/BC.